2019
DOI: 10.18632/aging.102484
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted brain functional hub and causal connectivity in acute mild traumatic brain injury

Abstract: There have been an increasing number of functional magnetic resonance imaging (fMRI) reports on brain abnormalities in mild traumatic brain injury (mTBI) at different phases. However, the neural bases and cognitive impairment after acute mTBI are unclear. This study aimed to identify brain functional hubs and connectivity abnormalities in acute mTBI patients and their correlations with deficits in cognitive performance. Within seven days after brain injury, mTBI patients (n=55) and age-, sex-, and educational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
2
20
1
Order By: Relevance
“…While several previous studies have successfully correlated their results with a decline in cognitive function (Li et al, 2019;Lu et al, 2019;Palacios et al, 2017), we did not find correlations between any other network and cognitive symptoms score. This may be in part attributed to the fact that the brain regions selected in these reports were not included in our study (e.g., frontal gyrus, substantia nigra, and temporal gyrus) as well as our smaller sample size.…”
Section: Correlation With Postconcussive Symptomscontrasting
confidence: 99%
“…While several previous studies have successfully correlated their results with a decline in cognitive function (Li et al, 2019;Lu et al, 2019;Palacios et al, 2017), we did not find correlations between any other network and cognitive symptoms score. This may be in part attributed to the fact that the brain regions selected in these reports were not included in our study (e.g., frontal gyrus, substantia nigra, and temporal gyrus) as well as our smaller sample size.…”
Section: Correlation With Postconcussive Symptomscontrasting
confidence: 99%
“…Some recent resting-state fMRI BOLD connectivity studies has identified disconnection functional coupling between the prefrontal cortex and these regions [40,41], which are consistent with our results. In addition, the CBF disconnection between the right CPL and bilateral ITG as well as the right FG was also been identified in mTBI patients, suggesting a disruption of the cerebellar-subcortical-cortical loop, which is partly consistent with the previous restingstate functional connectivity studies that indicate the CPL-FG disconnection and the abnormality of the cerebellum network in mTBI [42][43][44]. The disconnection of the cerebellum may be related to the functional deficits in cognitive integration in acute mTBI patients.…”
Section: Neural Plasticitysupporting
confidence: 84%
“…In line with these reports, we found that the left MFG appeared hyperconnected within the DMN in the mTBI patients in the acute stage, and this result could be interpreted as a compensatory reallocation or recruitment of cognitive resources. Meanwhile, our previous study used GCA to analyze the causal connections in the acute mTBI patients and demonstrated significantly increased connectivity from the left ACC to the left MFG 34 . For mTBI patients, Benier et al and Sharp et al hypothesized that such hyperconnectivity patterns in the DMN could be related to dysfunction in working memory and attention switching during cognitive demand 35,36 .…”
Section: Discussionmentioning
confidence: 99%